2003
DOI: 10.1016/j.ymthe.2003.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Transient increase in lung epithelial tight junction permeability: an additional mechanism for enhancement of lung transgene expression by perfluorochemical liquids

Abstract: Intratracheal instillation of perfluorochemical (PFC) liquids enhances lung epithelial transgene expression by improved vector propulsion throughout lung airways. We now demonstrate that PFC liquids also facilitate gene transfer by increasing transepithelial permeability. Apical application of PFC liquid to well-differentiated human airway epithelial cells resulted in a transient decrease in transepithelial resistance peaking approximately 2 h after PFC liquid administration and returning to normal approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Next, reagents such as EGTA that disrupt tight junctions have been shown to improve expression in the airways by exposing CAR on the basolateral surfaces of airway epithelium. Various PFC liquids have been utilized to improve expression in the distal airways of both healthy and diseased lungs [3, 610]. Our findings reflect at least two mechanisms thought to be involved with improved expression.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Next, reagents such as EGTA that disrupt tight junctions have been shown to improve expression in the airways by exposing CAR on the basolateral surfaces of airway epithelium. Various PFC liquids have been utilized to improve expression in the distal airways of both healthy and diseased lungs [3, 610]. Our findings reflect at least two mechanisms thought to be involved with improved expression.…”
Section: Discussionmentioning
confidence: 51%
“…Our findings reflect at least two mechanisms thought to be involved with improved expression. First, it has been previously shown that PFC liquid facilitates transient disruption of tight junctions, increasing exposure to CARs, that are distributed throughout the A549 cell membrane [3]. Second, based on the physicochemical property of this specific PFC liquid combination (with unique kinematic viscosity, vapor pressure, and lipophilicity profiles) [14, 36], the PFC suspension fosters increased and uniformed distribution of the virus relative to saline, such that more cells are exposed to virus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various strategies have been described, including pre-treatment with the Ca 2+ chelator EGTA [21], perfluorochemical liquid ventilant [29], and the detergents sodium caprate [30] and LPC [22]. LPC is a natural component of lung surfactant and is converted in the lung into phosphatidylcholine [31].…”
Section: Discussionmentioning
confidence: 99%